PENANAMAN NILAI-NILAI MODERASI BERAGAMA DALAM LINGKUP MASYARAKAT MAJEMUK - Alfrida Taruk Ponno; Reniati, Yiska Sambo, Sulianti Tangnga, Rianti Mean (CV. ADIBA AISHA AMIRA, 2023)
This research aims to analyze the strategies and effectiveness of instilling religious moderation values in the context of diverse communities. Religious moderation values encompass principles that promote tolerance, appreciation of diversity, and interfaith cooperation in addressing belief differences. The research methodology employed is qualitative research using a case study approach and document analysis, which was utilized to gain a comprehensive understanding of the implementation of religious moderation values in daily life. The research findings indicate that instilling religious moderation values can serve as a catalyst for building harmony and unity in diverse communities. Effective strategies include inclusive religious education, interfaith dialogue, and collaborative cross-faith activities. Furthermore, religious leadership capable of promoting equality and mutual understanding among faith communities also significantly contributes to creating an inclusive environment. This research provides valuable insights for the development of public policies and religious education programs aimed at strengthening tolerance and harmony in diverse communities. By prioritizing the cultivation of religious moderation values, communities can establish a solid foundation to achieve common goals in dynamic and diverse societal settings.